Assessing two-dimensional collisions second-years students using PhET simulations on momentum and impulse concept. Issue 1 (April 2021) - Adimayuda, R; Sari, L; Ismail, A; Amalia, I F; Gumilar, S; Samsudin, A
Abstract: Assessment is an important component in education that always needed. To improve the quality of education can be done by improving assessment learning quality and system. This study aims to determine the performance of students of grade X SMA N in Bandung West Java Indonesia school with 34 participants on a two-dimensional collision concept. This research is descriptive research which is conducted to examine the condition and situation that is happening, so that gives a fact-based description found in the school in other to find information factually. Problem studies that analyzed are the student's performance after using PhET simulations on two-dimensional collision concept. The instrument utilized in this study is a written test in the form of students' worksheets of momentum and impulse. Student worksheets test shows the average percentage on student performance in understandings concept of two-dimensional collision concept is 67.14%. These data indicated that student learning performance in good category. Learning by using virtual laboratory can provide more meaningful learning especially in physics concept that cannot be presented and observed directly in daily life.